2015
DOI: 10.1002/jnr.23684
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional or hyperfunctional? The amygdala in posttraumatic stress disorder is the bull in the evolutionary China shop

Abstract: Our motivation in writing this Review arose not only from the great value in contributing to this special issue of the Journal of Neuroscience Research but also from the desire to express our opinion that the description of the amygdala as "dysfunctional" in posttraumatic stress disorder (PTSD) might not be appropriate. We acknowledge that excessive activation of the amygdala contributes to the cluster of PTSD symptoms, including hypervigilance, intrusive memories, and impaired sleep, that underlies the devast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 133 publications
(151 reference statements)
2
36
0
Order By: Relevance
“…It is the 4 th most common psychiatric disorder, with a lifetime prevalence rate of 6.8% in the US [4]. The clinical manifestations of PTSD are characterized by intense fear, helplessness and horror following repeated experience of flashback memories and leads to elusive behavior [5, 6]. In the past decade extraordinary progress has been made to understand the pathogenesis of PTSD, but it is not yet completely clear [7].…”
Section: Introductionmentioning
confidence: 99%
“…It is the 4 th most common psychiatric disorder, with a lifetime prevalence rate of 6.8% in the US [4]. The clinical manifestations of PTSD are characterized by intense fear, helplessness and horror following repeated experience of flashback memories and leads to elusive behavior [5, 6]. In the past decade extraordinary progress has been made to understand the pathogenesis of PTSD, but it is not yet completely clear [7].…”
Section: Introductionmentioning
confidence: 99%
“…If we consider BDNF production as an important component of local synaptic structure, plasticity and overall functioning, then the imbalance of BDNF production between the hippocampus and amygdala would be consistent with our recent speculation regarding PTSD as an imbalance between amygdala and prefrontal cortical functioning (Diamond and Zoladz, 2016) We hypothesized that the hyper-functional status of the amygdala in PTSD is adaptive, from an evolutionary perspective, as a means with which to maintain heightened vigilance in a potentially hostile environment. The resistance of the amygdala to exhibit hypermethylation of the BDNF gene, and therefore to generate normal levels of BDNF, would enable this structure to continue to serve the function of maximizing one's vigilance, and to maintain memories of the trauma in an active state, following exposure to a life-threatening event.…”
Section: Accepted Manuscriptmentioning
confidence: 53%
“…The resistance of the amygdala to exhibit hypermethylation of the BDNF gene, and therefore to generate normal levels of BDNF, would enable this structure to continue to serve the function of maximizing one's vigilance, and to maintain memories of the trauma in an active state, following exposure to a life-threatening event. The differential expression of epigenetic modification to the hippocampus and prefrontal cortex versus amygdala may underlie the combination of amygdala-based hypervigilance and intrusive memories of trauma in conjunction with impaired hippocampal-prefrontal based processing of new information in people with PTSD (Diamond and Zoladz, 2016;Samuelson, 2011;.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Diamond and Zoladz described the amygdala in PTSD as ''the bull in the evolutionary China shop.'' 16 The misery experienced by the victim is a hyperfunctioning survival state that is abnormal under calm conditions. 16 In a 2008 article, Bryant, et al reported that approximately half of patients with PTSD did not respond to cognitive-behavioral therapy (CBT), which was considered the conventional treatment of choice at the time.…”
Section: Ptsdmentioning
confidence: 99%
“…16 The misery experienced by the victim is a hyperfunctioning survival state that is abnormal under calm conditions. 16 In a 2008 article, Bryant, et al reported that approximately half of patients with PTSD did not respond to cognitive-behavioral therapy (CBT), which was considered the conventional treatment of choice at the time. The researchers cited an excessive amygdala response to fear as a key factor in the suboptimal CBT success rate.…”
Section: Ptsdmentioning
confidence: 99%